A revelação do “quem” e o tornar-se pessoa: a constituição da personalidade no pensamento de Hannah Arendt - Santos, Juvercino Arcanjo dos (2019)
The Zeitgeist of contemporaneity more sharply than other times distance the individual interests of the higher activities in the individual. In this context, Hannah Arendt's claim has relevant prestige to think about the crises in the current context. Among the crises that bring us closer, that of personality - an element of idiosyncrasy in the subject - is perhaps the most significant although the least noticed. The purpose of this paper is to explore Arendt's notion of person, so as to demonstrate the dazzling of this individual element that each individual brings with him. The loss of this element is more noticeable with modernity, more markedly with the concentration camps, and in such a way that the way of life deprived of political freedom is reduced to the contemporaneousness of life, reduced to the maintenance of vital activities, an animal laborans, actions. To do so, we seek to verify the notion of becoming person involved with the activities of the spirit and the activities of the active life. This notion can be summed up as the choice of how one intends to appear in the public world of appearance. Rarely referred to by Arendt, but which arises from his speeches and conferences. In the first moment we approach the personality from types of person from the references of the activities of thought and judgment. Secondly, we seek to bring Arendt's phenomenology into the relation of thought and the appearance of the public world of politics, and for this it is necessary to go through the dismantling of the personality within the concentration camps and the victory of animal laborans, and we will finally analyze what this notion of person actually consists of and its relation to Arendtian ethics, fully demonstrated in moral personalities.